2001
DOI: 10.1055/s-0037-1616057
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Monoclonal Antibody against the Extracellular Domain of GPIbβ Modulates vWF Mediated Platelet Adhesion

Abstract: SummaryGPIb is disulfide-linked to GPIbα to form GPIb, a platelet receptor for von Willebrand factor (vWF). GPIb is in turn non covalently linked to GPIX and GPV to form the GPIb/V/IX complex. Apart from its contribution to controlling surface expression of the complex, the exact function of GPIbβ is not well established due to a lack of suitable ligands or antibodies. The present report describes a monoclonal antibody (RAM.1) that labeled the 26 kDa GPIbβ subunit on western blots and coprecipitated the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 45 publications
3
49
0
1
Order By: Relevance
“…30 This study extends our previous findings by providing evidence that targeting GPIbβ with RAM.1 inhibits VWF-induced GPIb signaling both in a human and in a mouse system, as shown by decreases in filopodia extension and intracellular Ca 2+ fluxes. Interestingly, RAM.1 also impacts on TF-and collagen-induced thrombin generation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…30 This study extends our previous findings by providing evidence that targeting GPIbβ with RAM.1 inhibits VWF-induced GPIb signaling both in a human and in a mouse system, as shown by decreases in filopodia extension and intracellular Ca 2+ fluxes. Interestingly, RAM.1 also impacts on TF-and collagen-induced thrombin generation.…”
Section: Discussionsupporting
confidence: 88%
“…Its binding to GPIbβ could alter the organization of the GPIb-IX complex within the plasma membrane and in turn reduce the binding properties of GPIbα, which would result in the transmission of a weaker signal. 30 Alternatively, a change in conformation could disturb interaction of GPIb-IX with intracellular partners involved in GPIbmediated signaling. This hypothesis could be supported by observation that RAM.1 promotes dephosphorylation of S166 in the intracytoplasmic domain of GPIbβ, a site implicated in 14-3-3 binding.…”
Section: Igg Indicates Immunoglobulin Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, it is possible that phosphorylation at Ser 166 directly or indirectly induces a conformational change in the extracellular ligand-binding domain of GPIb␣. This possibility is consistent with a recent report that an anti-GPIb␤ monoclonal antibody causes inhibition of the ligand-binding function of GPIb-IX (43). Thirdly, as we showed previously that association between GPIb-IX and the membrane skeleton regulates ligandbinding function (38), it is also possible that phosphorylation of GPIb␤ induces reorganization of the GPIb-IX-associated membrane skeleton, which in turn regulates the VWF-binding function of GPIb-IX.…”
Section: Figsupporting
confidence: 92%
“…To the latter, several lines of evidence showed that when specific antibodies were used to pull down the GP Ib-IX complex, the major dimeric form is ␣/␤, instead of ␣/␣ or ␤/␤ (3,34). Because our data indicated that the ␣/␤ disulfide linkage is the major force mediating GP Ib␣ into the GEMs, an interaction being essential for platelet adhesion and platelet activation upon vWf engagement (9), an enzymatically controlled preference for ␣/␤ disulfide bond formation, as opposed to other combinations (e.g.…”
Section: Discussionmentioning
confidence: 99%